تعليم الحوار العربي باستخـدام وسيلة الــرســوم الهـزليـة - Ade Arip Ardiansyah (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
One of Vailable strategis to creat effective learning is learning bu using media. Comic as media of communication, has adjuzted ability in wich can be used for several objectives. The purpose of this study was to find out the value of students in learning Arabic al-hiwār material before and after using comic media in grade 7 students at MTS Darul Ulum PUI Majalengka. The method used in this study is an experimental method with the design of one group pre-test and post-test design. The techniques used in data collection are interviews, observations, and tests. The results of this study note that the value of students in learning Arabic al-hiwar material before using comic media obtained an average yield of 57,24 and the value of students in learning Arabic al-hiwar material after using comic media obtained an average yield of 72,24. Thus, the use of comic media in learning Arabic language al-hiwar material has an influence in increasing the value of students by a percentage of 35%.